Digital Shadowing with Mobile Tools for Improving Second Language Acquisition - Wahyudi Syaputra (LIMEEMAS: Jurnal Ilmiah Pendidikan, 2026)
Vocabulary mastery is fundamental in learning English as a foreign language (EFL). However, many learners struggle to increase the number of words and use vocabulary effectively. This study explores the effectiveness of mobile technology-based shadowing techniques in improving EFL learners' vocabulary mastery. This study uses mixed methods with an experimental approach. A total of 40 intermediate EFL participants from the Domestic English Course in Kampung Inggris Pare were selected through purposive sampling and participated in a shadowing practice program using mobile applications such as Google Voice Assistant and Duolingo for four weeks. Quantitative data was obtained from pre-test and post-test, while qualitative data was collected through questionnaires and interviews. The results of the t-test statistical test produced a value of t = -26.502, with a degree of freedom (df) of 30 and a significance value (Sig. 2-tailed) of 0.000. This p-value is smaller than 0.05, indicating that the difference between pre-test and post-test scores is statistically significant. Thus, the treatment provided to help students learn English vocabulary effectively and authentically improves their abilities. Interviews revealed that ease of access, flexibility, and repetitive practice supported this method's success despite obstacles like audio speed and internet network limitations. Thus, mobile technology-based shadowing techniques can be innovative in improving EFL learners' vocabulary mastery.